Correlation of disease activity score using erythrocyte sedimentation rate and C-reactive protein with clinical disease activity index in rheumatoid arthritis patients - Viraj Panchal; Puja Srivastava; Dhaiwat Shukla; Devang Rana; Supriya Malhotra; Sapan Pandya (Indian Journal of Rheumatology)
Background: Most patients coming to government hospital are from lower socioeconomic class and do not always get investigations done like ESR or CRP. A purely clinical index like CDAI would be a useful measure in such resource poor settings. Also there is scarce data on patterns of DMARD use from our country. Objectives: To compare Disease Activity Score 28 using erythrocyte sedimentation rate (DAS28-ESR) and Disease Activity Score 28 using C-reactive protein (DAS28-CRP) with CDAI (Clinical Disease activity index) as measures of disease activity of RA and to analyze prescription patterns in RA patients. Methods: Ours was a cross-sectional study of 4 months' duration. DAS28-ESR, DAS28-CRP and CDAI were calculated. The details of DMARDs used were recorded in proformas. Correlation was done using Spearman's Correlation Coefficient Test. To assess agreement between scores Cohen's kappa value was also evaluated. P value obtained <0.05 was considered significant. Results: We evaluated a total of 104 patients most of them being females with a mean age of 45 years. The mean DAS28-ESR was 4.59 ± 1.36, mean DAS28-CRP was 3.86 ± 1.25 and mean CDAI was 16.9 ± 9.26 . The correlation coefficients of DAS28-ESR with DAS28-CRP was 0.894, DAS28-ESR with CDAI was 0.886 and DAS28-CRP with CDAI was 0.910. Methotrexate was the most prescribed drug as a mono therapy or in a combination with Hydroxychloroquine followed by Leflunomide, Sulfasalazine, and Prednisolone in that order. Conclusion: The CDAI can substitute for SDAI or DAS 28 ESR/CRP and this would be very useful in a resource poor setting. Methotrexate was the most prescribed drug in our set up as mono or combination therapy.